Personalized Marketing and Customer Retention: The Mediating Role of Customer Satisfaction - Alvin Lesmana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the effect of personalized marketing on customer satisfaction and customer retention, as well as to explain the role of customer satisfaction as a mechanism linking marketing personalization to customers’ decision to remain with a brand. The background of this study is based on the increasing use of data-driven marketing strategies, product recommendations, personalized promotions, and digital communication tailored to customer preferences. In an increasingly competitive business environment, companies are required not only to attract new customers but also to retain existing customers through relevant, convenient, and valuable experiences. This study employed a quantitative explanatory approach, with the population consisting of customers who had received personalized marketing from a particular company or brand. The sampling technique used was purposive sampling, with the criteria that respondents had received personalized promotions and had made repeat purchases. The total sample consisted of 110 respondents. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling. The findings show that personalized marketing has a positive and significant effect on customer satisfaction. This indicates that promotions, recommendations, and marketing messages that are relevant to customer needs can create more positive customer experiences. Customer satisfaction is also found to have a positive and significant effect on customer retention, meaning that satisfied customers are more likely to make repeat purchases, continue using products or services, and avoid switching to competitors. In addition, personalized marketing has a direct effect on customer retention, although its effect becomes stronger when mediated by customer satisfaction. The implications of this study emphasize that companies need to develop personalization strategies that are not only data-driven but also relevant, ethical, non-intrusive, and oriented toward customer value. Therefore, personalized marketing can serve as an important strategy for improving customer satisfaction and maintaining long-term customer retention.